CIPP BASED EVALUATION OF THE WIRAUSAHA MERDEKA PROGRAM AS ENTREPRENUERSHIP EDUCATION IN HIGHER EDUCATION INSTITUTIONS : - Andi Ibrahim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Entrepreneurship plays a strategic role in fostering national economic growth through job creation and innovation development. In higher education, entrepreneurship programs such as Wirausaha Merdeka are designed to strengthen students’ entrepreneurial competencies through experiential learning and business incubation. However, the effectiveness of such programs requires comprehensive evaluation. This study aims to evaluate the implementation of the SEMESTA (Sebelas Maret Startup Academy) program at Universitas Sebelas Maret using the CIPP (Context, Input, Process, Product) evaluation model. This research employs a qualitative evaluative approach. Data were collected through in-depth interviews, participatory observation, and documentation involving program managers, mentors, students, and industry partners. The findings indicate that the program has strong contextual relevance, adequate resource readiness, well-structured implementation processes, and measurable outcomes in the form of startup development and increased entrepreneurial competencies. The study contributes theoretically to the application of the CIPP model in entrepreneurship education and provides practical recommendations for improving incubation programs in higher education.